Aldolase A and Phospholipase D1 Synergistically Resist Alkylating Agents and Radiation in Lung Cancer - Chang, Yu-Chan; Chang, Peter Mu-Hsin; Li, Chien-Hsiu; Chan, Ming-Hsien; Lee, Yi-Jang; Chen, Ming-Huang; Hsiao, Michael (Frontiers in Oncology, 2022)
Exposure to alkylating agents and radiation may cause damage and apoptosis in cancer cells. Meanwhile, this exposure involves resistance and leads to metabolic reprogramming to benefit cancer cells. At present, the detailed mechanism is still unclear. Based on the profiles of several transcriptomes, we found that the activity of phospholipase D (PLD) and the production of specific metabolites are related to these events. Comparing several particular inhibitors, we determined that phospholipase D1 (PLD1) plays a dominant role over other PLD members. Using the existing metabolomics platform, we demonstrated that lysophosphatidylethanolamine (LPE) and lysophosphatidylcholine (LPC) are the most critical metabolites, and are highly dependent on aldolase A (ALDOA). We further demonstrated that ALDOA could modulate total PLD enzyme activity and phosphatidic acid products. Particularly after exposure to alkylating agents and radiation, the proliferation of lung cancer cells, autophagy, and DNA repair capabilities are enhanced. The above phenotypes are closely related to the performance of the ALDOA¬/PLD1 axis. Moreover, we found that ALDOA inhibited PLD2 activity and enzyme function through direct protein–protein interaction (PPI) with PLD2 to enhance PLD1 and additional carcinogenic features. Most importantly, the combination of ALDOA and PLD1 can be used as an independent prognostic factor and is correlated with several clinical parameters in lung cancer. These findings indicate that, based on the PPI status between ALDOA and PLD2, a combination of radiation and/or alkylating agents with regulating ALDOA-PLD1 may be considered as a new lung cancer treatment option.